A Study on the Influencing Factors of Consumers' Purchase Intention During Livestreaming e-Commerce: The Mediating Effect of Emotion - Zhou, Rong; Tong, Lei (Frontiers in Psychology, 2022)
With the deep popularity of mobile Internet, the "eyeball economy" is more active than ever. Driven by powerful modern media, live streaming, as a new form of attracting public attention to obtain economic benefits, is worth studying its influence path on consumers. Based on the technology acceptance model and the mediating effect of emotion, this study constructs the consumer influencing factor model of live streaming e-commerce. The research model and related hypotheses are verified by SPSS and Linear Multiple Regression models. The research found that, emotional trust and perceived emotional value could be regarded as mediating variables to stimulate consumers' purchase intention in livestreaming e-commerce. They have a full mediating effect on product and atmosphere and a partly mediating effect on homogeneity and promotion, which identifies that online celebrity’s homogeneity and sales promotion could influence consumers' purchase intention through the partly mediating role of emotional trust and perceived emotional value while product and atmosphere induced by emotional contagion could exert influence on consumers’ purchase intention through the full mediating effect of emotional trust and perceived emotional value.